Agrobiodiversity of Home Gardens in Selected Marginal Upland Villages of Inopacan, Leyte, Philippines - Belonias, Beatriz S.; Platino, Czarina S.; Malanguis, Jessa T. (Annals of Tropical Research, 2014)
Home gardens are subsistence crop production systems that significantly contribute to the socio-ecological resilience of peasant communities reducing vulnerability and ensuring food security. Because of their small size, they are neglected repositories of biological diversity. This paper describes the agrobiodiversity and management of home gardens in about 79 households in three marginal upland villages of Inopacan, Leyte. Semi-structured interviews and actual home garden visits were done to collect data. Results show that home gardens studied had high species diversity and exhibited a multilayered structure. A total of 171 species in 74 families and 146 genera were documented. The composites (Asteraceae) had the most number of genera and species followed by the orchids (Orchidaceae), legumes (Fabaceae) and aroids (Araceae). More than 70% of the species were exotics which were mostly ornamental plants. Erect herbs were the most common, followed by trees, shrubs, herbaceous vines and epiphytes. Majority of the species were ornamentals followed by fruit trees, medicinal plants, vegetables and spice plants, grown primarily for home use (62%) rather than as source of income. Established and managed by family members who provide free labor, the gardens mostly utilized cost–free planting materials and with no fertilizer or pesticide application.